Penerapan Restorative Justice dalam Perkara Perselingkuhan Anggota Kepolisian - Pardi Musa; Kamaruddin; Huzaiman Huzaiman (CV Rewang Rencang, 2025)
This study examines the application of restorative justice in cases of infidelity involving members of the police. Traditional retributive approaches are often ineffective in resolving these problems, so more constructive alternatives are needed. This research uses a doctrinal research method with a conceptual approach. The results show that the application of restorative justice can help improve relationships between members and restore public trust in institutions. This approach encourages dialogue and reconciliation, enabling all parties involved to participate in the settlement process. Challenges in implementing restorative justice in the police include hierarchical institutional culture and negative stigmas related to infidelity.